In-grain phase separation and structural ordering in Fe–Ga alloys seen from reciprocal space. (January 2021) - Balagurov, A.M.; Chernyshov, D. Yu; Bosak, A.А.; Bobrikov, I.A.; Sumnikov, S.V.; Golovin, I.S.
Abstract: Single crystal synchrotron diffraction was used for detailed analysis of ordering effects in alloys with a nominal composition of Fe80.5 Ga19.5 and Fe73.1 Ga26.9 . The first composition manifests a disordered average A2 structure with local fluctuations resembling a D03 ordering motif in the lengthscales of ~50 Å. In Fe73.1 Ga26.9 alloy ordered over a long range, a D03 matrix coexists with ~100 Å inclusions of a new ordered phase, presumably hexagonal with lattice parameters a ≈ 8 a 0 and c ≈ 12 a 0, where a 0  = 2.87 Å is the unit cell dimension of body-centered cubic Fe. Graphical abstract: Image 1 Highlights: Fe80.5 Ga19.5  and Fe73.1 Ga26.9  single crystal grains extracted from polycrystalline ingots. The long-range structure of Fe–19Ga corresponds to a disordered A2 with ~50 Å precursors to D03 . Fe–27Ga stabilizes the D03  structure with nanoscale (~100 Å) precipitates of a new phase. 3D mapping of reciprocal space, azimuthal maps and Gandolfi patterns from single grains of polycrystalline aggregates.